Debat Retorika dalam Wacana Islam Nusantara - Dini Safitri (Universitas Al Azhar Indonesia, 2015)
The purpose of this study was to describe rhetorical war in Islam Nusantara. Islam Nusantara is an assimilation of cultures that occured in Indonesia since Islam came to the archipelago. But in a text production in social media, lots of pros and cons are re garding to the practice of cultural assimilation with Islamic values. The text of among one another in their argumentation has been like being at war to persuade the reader. The author uses a qualitative methodology to analyze the rhetoric about the texts. The result showed that the text of the war occurred because of differences in perspective created by the structure of the Islamic organizations in Indonesia.